EMPLOYEES TRAINING: AN INGREDIENT OF ORGANIZATIONAL SURVIVAL IN NIGERIA (A STUDY OF SELECTED SMALL AND MEDIUM SCALE ENTERPRISES IN PORTHARCOURT) - DIALOKE, ASS. PROF. IKECHUKWU,; EBIKESEYE, BIPELEDEI, (IJRDO - Journal of Applied Management Science, 2017)
This study examined Employees Training: An Ingredient of Organizational Survival in Nigeria with Selected Small And Medium Scale Enterprises in Portharcourt as its case study. the study was guided by three research questions and hypotheses which are consistent with its objectives. The study employed the descriptive survey approach in its design and data was generated from a five point likert scale questionnaire. The study covered a population of one hundred and forty three (143) employees of eight (8) SMEs within Portharcourt city. The researcher used purposive sampling technique to select 129 respondents as the sample; however, out of the 129 questionnaires distributed, only 112 were correctly filled and returned; thereby given a questionnaire return rate of 87%. The statistical tools used for data analysis is the Mannwhitney U test using the 20.0 version of statistical package for social sciences (SPSS). It was conclude that bearing the strategic contributions of employee training, training of employees should not just be seen as a fringe benefit for the individual staff by the organization or an interventionist approach to temporarily solve organizational problems. Rather, they should be seen as an integral part of business functions that build a long-term strategic value for the organization by helping the manpower acquire relevant skills, knowledge and experience that can help the organizations attain their long term goals. The study recommended that the cost of employee training in the SMEs should be controlled, in order to ensure that it does not negate the competitiveness of the organization. These SMEs in related businesses can achieve by jointly building training schools in order to attain and maximize economies of scale, there is need to ensure that training programmes are tailored along the skill gaps of the employees. This will ensure that the employees contribute maximally to the sustainability of SMEs and that to ensure that employee training contributes maximally to SMEs adaptability, the updating of workers’ skill must be anchored on needs assessment, this will enhance the inclusion of current and relevant skills in the training scheme of SMEs